Strengthening Students’ Akhlakul Karimah in Building the Foundation of Islamic Education at Madrasah Aliyah - Ma'rifatul Ulum; Ridho Riyanto (Golden Ratio of Data in Summary, 2026)
This study aims to analyze the strengthening of akhlakul karimah (noble character) among students in building the foundation of Islamic education at Madrasah Aliyah PP Al-Ihslah Saren Bandar. The background of this research is rooted in the challenges posed by the rapid development of technology and information, which significantly influence students’ behavior and morality, making character reinforcement increasingly essential. This study employs a descriptive qualitative approach with a case study design, involving teachers, the madrasah principal, and boarding school caregivers as key informants. Data were collected through interviews, observations, and documentation, and subsequently analyzed using descriptive techniques. The findings reveal that the strengthening of akhlakul karimah is implemented through interactive Islamic Religious Education (PAI) learning, the habituation of moral values within the boarding school environment, supervision of technology use, and the active involvement of all educational stakeholders. This study demonstrates that strengthening noble character can establish a solid foundation for Islamic education that is adaptive to contemporary developments and capable of shaping students into disciplined, honest, responsible, and socially caring individuals.